2009
DOI: 10.1055/s-0029-1214643
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the utility of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) in pancreatic masses, using a 22-gauge or 25-gauge needle system: a multicenter experience

Abstract: This retrospective comparative study shows that EUS-FNA with a 25-gauge needle system is a safe and reliable method for tissue sampling in pancreatic masses. The system is more sensitive and has a slightly [corrected] higher NPV than the standard 22-gauge needle. Our study suggests that perhaps the smaller caliber FNA needle causes less trauma during EUS-FNA and hence less complications. Further studies including randomized trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 4 publications
0
76
0
1
Order By: Relevance
“…The median number of patients included in each study was 151 (range 27-557), and the median study length was 44 (11-119) months. The median STARD score for the articles was 17 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). One study reported separate results for EUS-FNA performed with 22-gauge and 25-gauge needles, and these were included in the analysis as separate studies.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The median number of patients included in each study was 151 (range 27-557), and the median study length was 44 (11-119) months. The median STARD score for the articles was 17 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). One study reported separate results for EUS-FNA performed with 22-gauge and 25-gauge needles, and these were included in the analysis as separate studies.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…One study reported separate results for EUS-FNA performed with 22-gauge and 25-gauge needles, and these were included in the analysis as separate studies. 15 …”
Section: Systematic Reviewmentioning
confidence: 99%
“…Various techniques have been described to optimize accuracy, efficiency, and quality of EUS-FNA specimens. FNA is typically performed using a 22-or 25-gauge needle with a stylet under EUS guidance [9][10][11][12][13][14][15]. There are several variables that impact the overall diagnostic yield of EUS-FNA such as skill and experience of the endosonographer and cytopathologist, type and diameter of the needle, ability to puncture the lesion, use of aspiration/suction as opposed to reliance on the capillary and shearing action of the needle, number of passes performed, sample preparation, immediate cytologic evaluation in the procedure room, and pathologic interpretation [10,[16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reported variables that affect the overall diagnostic yield of EUS-FNA such as the skill and experience of the endosonographer and the cytopathologist, the diameter of the EUS-FNA needle, the use of suction as opposed to reliance on the capillary and shearing action of the needle, the number of passes, and availability of immediate on-site cytopathology assessment. [12][13][14][15][16][17][18][19][20] It is routine practice for most endosonographers to perform EUS-FNA by using a 22-or 25-gauge needle with an internal stylet, and, in fact, all commercially available EUS-FNA needle systems include a removable stylet. There is a theoretical belief that the use of a stylet prevents clogging of the needle lumen by the GI wall tissue as the needle traverses this to reach the target lesion, which could limit the ability to aspirate cells from the target lesion.…”
mentioning
confidence: 99%